Asymmetric hybrid multilevel inverter with reduced harmonic using hybrid modulation technique - Satish Kumar; M. Sasi Kumar (Institute of Advanced Engineering and Science, 2020)
This paper studies the Asymmetric cascaded three phase multilevel inverter developed with hybrid modulation technique applied for an industrial application. The aim of this paper to reduce the Total harmonics distortion in the cascaded multi level inverter by introducing the new concept to develop the three phase CMLI. This inverter has two segments, one segment has H-bridge inverter and another segment has sequential arrangement of power semi conductor switches with asymmetrical voltage source in the ratio of 1:2. Similarly develop the segments for other phases. This new topology is called as Hybrid MLI. This hybrid MLI is used to reduce the no of semiconductor device requirement and the Total harmonics distortion. The inverter is controlled by Phase disposition (PD) and alternative phase opposition disposition PWM technique (APOD). This control technique is used to minimize the current harmonic and increase the system performance. The circuit is simulated using Matlab circuit and its performance is compared using PD and APOD PWM techniques and verified with simulation results.